GPS loss of lock statistics over Brazil during the 24th solar cycle. Issue 2 (15th July 2020) - Damaceno, Juliana G.; Bolmgren, Karl; Bruno, Jon; De Franceschi, Giorgiana; Mitchell, Cathryn; Cafaro, Massimo
Abstract: A statistical analysis of Loss of Lock (LoL) over Brazil throughout the 24th solar cycle is performed. Four geodetic GPS dual-frequency (L1, L2) receivers, deployed at different geographic latitudes ranging from about 25° to 2° South in the eastern part of the country, are used to investigate the LoL dependence on time of the day, season, solar and geomagnetic activity. The results of the analysis show that LoL is most likely in the post-sunset hours during summer and equinox, especially within the southern crest of the Equatorial Ionospheric Anomaly (EIA), in a region between about 10°S and 25°S of geographic latitude, matching the typical behaviour of scintillation over Brazil. This is confirmed by the correlation found between the relative occurrence of LoL (LoL (%)) and the Rate Of TEC Index (ROTI), used as a proxy of scintillation index and calculated for each receivers along the entire period of investigation. The LoL (%) for given solar and geomagnetic indices show some correlation with increasing the severity of the index. This correlation is strongest in the area of the southern crest of the EIA, while there is little to no apparent impact closer to the equator, depending on the index. LoL (%) increases with increasing geomagnetic disturbances, varying between 1% and 10% for AE ranged between 400 and 1200 nT, and exceeding 3% when Dst is around −100 nT, both related to moderate-severely disturbed conditions.